Soil Pile Set-Up Of Driven Pile In Clay - Ng, Wen Kuan (2013)
Soil/ pile set-up is a phenomenon of pile capacity increase in a driven pile as time passes which is often ignored. Incorporation of set-up effect in routine designing of piles could result in saving due to smaller required section or lesser driving energy. This research was carried out to study if small cylindrical metal piles with diameters ranging from 12.0 mm to 75.5 mm that were driven in the field and cylindrical metal rods with diameters ranging from 9.4 mm to 25.6 mm that were tested in laboratory, were capable of measuring set-up parameters of actual working piles and determining factors that affect set-up in clays. The field tests have involved depths ranging from 1.0 m to 9.8 m and periodical data readings of up to 350 days while the laboratory tests have had 450 mm of horizontal penetrations and data collection for up to 28 days. In addition, the field tests have also included square reinforced concrete piles, 300 mm to 400 nun in thicknesses, and driven to a depth of9 m. Two sites have been used for the tests namely within the campuses of Universiti Sains Malaysia in Nibong Tebal, Pulau Pinang and Universiti Teknologi Mara in Permatang Pauh, Pulau Pinang.